ANALISIS EFEKTIVITAS SISTEM INFORMASI MANAJEMEN PENERIMAAN PENGELOLAAN PERMOHONAN ADMINISTRASI KEPENDUDUKAN (SIMP3AK) PADA DINAS PENCATATAN SIPIL KOTA MAGELANG - Panji Afandi; Ghina Fitri Ariesta Susilo (Faculty of Economics and Business, Universitas Warmadewa, 2021)
This..study..aims..to determine..the..effectiveness of the Management Information..System for Receiving Management of..Population..Administration Requests (SIMP3AK) at the..Magelang City Civil Registry Office. Data collection using interview, observation and documentation techniques. The accuracy of the data from the Management Information System for Receiving Management of Population Administration Requests (SIMP3AK) is considered..to..be..more..accurate..when..compared..to..the..manual system, because all population data is stored in a data base, so that when the population data is needed the operator only needs to access the existing data. But there are still weaknesses of the SIMP3AK program, namely there are population data errors, photo errors with the data listed. The..implementation of the Management Information System for Acceptance of Management of Population Administration Requests (SIMP3AK) at the Magelang City Civil Registry Office has been going well, although there are still some shortcomings. It is expected that services to the community especially population administration can be better and maximal.